The Effect of Internal Audit and Internal Control on Fraud Prevention: Empirical Study at Digital Service Head Office of PT Bank BCA BSD - Lukman, Christylia Gita Fairy; Subiyanto, Bambang; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to examine factors that affect fraud prevention or fraud actions. The variables used in this study are internal audit, internal control, and fraud prevention. The type of data used in this study is quantitative data with primary data sources. The population in this study is workers at PT Bank BCA's Digital Service Head Office in BSD. The statistical tool used to test this hypothesis is multiple linear regression analysis with the help of the SPSS ver 25 application. Primary data in this study was obtained by distributing questionnaires to respondents and processed with a total of 70 questionnaires. These results show that from 2 hypotheses, they have positive and significant results and all are supported by data.